Os (in)sofismáveis caminhos do storytelling : Woody Allen e o documentário ficcionado - Chinita, Fátima (2013)
ABSTRACT: Between pure documentary and pure fiction there are, more and more, a reasonable number of cinematic alternatives that convey a dimension of non-reality. Between the pointedly factual discourse and the irrational belief in an entirely narrative world, there intervenes an informed conviction in a truthful but nonexistent universe, in which the formal enunciation sells an image of objectivity. In a path that leads us from the forms and contents of reflexive and performative documentaries, according to Bill Nichols, and ends up in fake documentary itself, we will have the opportunity to stress the filmic construction and its inherent narrative purpose, be it a fictional story or the creator himself as character (others would say subject) of the cinematic construct. In a boomerang kind of logic, the more the objects direct us to a referent, the more they restore us a creative/authorial reference and, along with it, the narrative idea that instills it. In Woody Allen’s case, this storytelling manifests itself in the fake documentary genre, which works as if it is the reality, only to better manifest the sole reality that interests the director: that of the metacinema, or the cinema as self-referencial reality. The practical examples will be derived from the following films: Take the Money and Run (1969) e Husbands and Wives (1992).